2020
DOI: 10.1186/s12958-020-00626-8
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-releasing hormone agonist combined with hormone replacement therapy does not improve the reproductive outcomes of frozen-thawed embryo transfer cycle in elderly patients: a retrospective study

Abstract: Background With the rapid development of whole embryo freezing technology, more and more frozen-thawed embryo transfer (FET) was used in assisted reproductive technology. However, the best FET program for elderly women has not been finalized. We intended to explore the reproductive outcomes of traditional hormone replacement treatment and a gonadotropin-releasing hormone agonist (GnRHa) combined with hormone replacement treatment in the frozen-thawed embryo transfer cycle of elderly patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
2
16
1
Order By: Relevance
“…An interesting observation in our study is that the mean level of progesterone on the administration day in the HRT cycle was signi cantly higher than that in the GnRHa-HRT cycles (0.38±0.29 versus 0.53±0.47, P=0.001), which is consistent with the results in previous studies [12,14,22] . This might be due to a premature rise of LH levels in hormonal stimulation protocol without a GnRH agonist, which negatively alters the receptive window of the endometrium [16] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An interesting observation in our study is that the mean level of progesterone on the administration day in the HRT cycle was signi cantly higher than that in the GnRHa-HRT cycles (0.38±0.29 versus 0.53±0.47, P=0.001), which is consistent with the results in previous studies [12,14,22] . This might be due to a premature rise of LH levels in hormonal stimulation protocol without a GnRH agonist, which negatively alters the receptive window of the endometrium [16] .…”
Section: Discussionsupporting
confidence: 92%
“…Pretreatment with GnRHa before HRT in FET cycles is considered to be ineffective for the elderly patients, but it could be effective for the patients with RIF [12] . Recent studies also failed to demonstrate any signi cant effect of depot GnRHa-FET protocol in the live birth/ongoing pregnancy rate [6] .…”
Section: Discussionmentioning
confidence: 99%
“…There is insufficient evidence that the use of a depot GnRH agonist combined with an HRT cycle is better or worse than the NC or HRT protocol for reproductive outcomes in FET cycles, especially for patients with RIF. Pretreatment with a GnRH agonist before HRT in FET cycles is considered ineffective for patients of advanced reproductive age, but this does not include patients with RIF [ 16 ]. A recent study also failed to demonstrate any significant effect of a depot GnRH agonist–HRT protocol on the live birth/ongoing pregnancy rate for patients with RIF [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only three studies considered live birth rate as outcome, and our results were consistent with our previous study focus on elderly patients and another retrospective study. In those two studies, the use of GnRH agonist in arti cial endometrium cycles to increase live birth rates cannot be established 21,22 . Another prospective randomized trial we mentioned above has concluded that the supplement of GnRH agonist associated with higher live birth rates 9 .…”
Section: Discussionmentioning
confidence: 99%